End-fire multibeam radial line slot array antennas - Teddy Purnamirza; Junisbekov M. Shardarbekovich; Riza Adi Jaya; Imran Mohd Ibrahim; Kabanbayev A. Batyrbekovich; Depriwana Rahmi (Universitas Ahmad Dahlan, 2024)
This research proposed and verified a novel method in realizing end-fire radial line slot array (RLSA) antennas. This method involved the use of high beamsquint values in the design of slot pairs, which aimed to shift the antenna’s beam toward the end-fire direction. Furthermore, identical slot pairs were also placed in the antenna’s background to further squint the beam in the end-fire direction. By using this method, forty multibeam end-fire RLSA antennas were modeled and simulated to determine the most efficient model to be fabricated. The accuracy of the simulations was confirmed through measurements taken from the fabricated prototype, which demonstrate good agreement with the simulation results and confirm the validity of the proposed method. The result showed that it is possible to design four end-fire beam antennas with a gain of 8 dBi, directions of 0°, 90°, 180°, and 270° in the azimuth direction, and a beamwidth of about 20°. The antenna also showed low reflection and bandwidth of about 500 MHz, which is suitable for Wi-Fi applications.